Stabilization and Solidification of Sludges - Nor Azalina, Rosli; Hamidi, Abdul Aziz; Leonard Lim, Lik Pueh; Inawati, Othman; Jethro, Henry Adam; Yung-Tse, Hung (Springer, Cham, 2024)
Stabilization and solidification is a treatment process for reducing the toxicity and binding hazardous substances contained in wastes, such as sludge, from leaching into the environment. The stabilization and solidification of sludge enable the reuse and recycling of sludge from being disposed into the landfill, a paradigm shift in the waste management hierarchy. Due to the variation of sludge properties (including toxicity) and reuse application, it is important to understand the mechanism and techniques of stabilization and solidification of sludge, as well as the roles of material and factors affecting the reaction when considering the potential for reusing a sludge. A key to determining the compatibility and proportioning of material for the stabilization and solidification of sludge is basically based on the chemical composition of calcium and silica in the mixture for forming calcium silicate hydrate (CSH) gel and CH crystal, which contributes to the strength. Among the characteristics of stabilized and solidified sludge to be investigated are optimum moisture content (OMC), strength, hydraulic conductivity, plasticity and immobilization of heavy metals, depending on the intended application, such as alternative construction material or landfill cover. The potential reuse of sludge as alternative construction material and landfill cover is discussed.